Normative data and physical determinants of multiple sprint sets in young soccer players aged 11-18 years - Selmi, M. A.; Sassi, R. H.; Yahmed, M. H.; Giannini, S.; Perroni, F.; Elloumi, M. (The Journal of Strength and Conditioning Research, 2020)
The aims of the study were: (a) to establish normative data for repeated-sprint sets (RSS) test based on the maturity status (age at peak height velocity [PHV]) and (2) to investigate the relationship between anthropometrical variables (stature, sitting height, body mass, and body fat percentage), RSS (2 × 5 × 20 m with 15-second recovery between sprints and 1-minute recovery between sets), and fitness tests {squat jump, countermovement jump, standing long jump, standing triple jump, 5-jump test, and 20-m shuttle run (multistage shuttle run test [MSRT])}. Young male soccer players (n = 262; age: 14.5 ± 2.9 years) were evaluated and classified into 4 groups according to their maturity status: pre-PHV, circum-PHV1, circum-PHV2, post-PHV. An analysis of variance and Bonferroni post hoc were used to determine maturity group differences (p = 0.05), whereas Pearson's correlation was used between variables. Repeated-sprint sets' indices (sum of sprint times [SST] and best sprint time [BST]) were significantly different between the maturity groups. Significant correlations between SST with body mass (from -0.73 to -0.33) and MSRT (from -0.49 to -0.30) among each maturity group were found. With the different maturity groups, correlations between SST (s), BST (s), and vertical jump (cm) (r = -0.63 to -0.25 and r = -0.68 to -0.23) and horizontal jump (m) (r = -0.70 to -0.38 and r = -0.63 to -0.43) were observed. Repeated-sprint sets' values improve during maturation of young soccer players and the correlations between RSS and fitness tests vary through the maturity groups. This information could be useful for the coach to identify talent and to prescribe specific physical training to improve performance.